High-Resolution Mapping of Seagrass Biomass Dynamics Suggests Differential Response of Seagrasses to Fluctuating Environments - Chen, Kuan-Yu; Lin, Hsing-Juh (Diversity (Basel), 2022)
Seagrass beds are major blue carbon ecosystems. Climate change-associated factors may change the seagrass community and affect the capacity of carbon sequestration. To explore the possible effects of warming, higher precipitation levels and/or sea level rise on seagrasses, the spatial and seasonal dynamics in shallow seagrass beds comprising the late-successional seagrass Thalassia hemprichii and the early-successional seagrass Halodule uninervis were tracked. The high-resolution mapping of seagrass biomass dynamics showed that T. hemprichii was the dominant species in the study sites year round, as the space occupation by the larger seagrass T. hemprichii was more efficient than that by the smaller seagrass H. uninervis. The space occupation by both species in the low-elevation site was more efficient than in the high-elevation site. In the low-elevation site, while the dominance of the faster growing seagrass H. uninervis was increasing, the dominance of T. hemprichii was decreasing. This suggested that the carbon sequestration capacity of the seagrass beds will decrease, as T. hemprichii was capable of storing more carbon in the sediments. In the high-elevation site, however, the distribution of both species was distinct and showed a clear seasonal succession. The dominance of H. uninervis moved to shallower water in the wet season and then moved back to deeper water in the dry season. Our observations suggested that four possible mechanisms might be involved in the dominance shift in the shallow seagrass beds: (1) the deeper water in the low-elevation site or the higher precipitation levels in the wet season might reduce the drought stress of H. uninervis at low tide and enhance the competition of H. uninervis over T. hemprichii; (2) the growth of H. uninervis might be stimulated more by the flushing of land-based nutrients caused by the higher precipitation rates in the wet season; (3) in the high-elevation site, the faster flow velocity and frequently disturbed sediments in the dry season might constrain the further expansion of H. uninervis to shallower water; (4) the faster flow velocity in the high-elevation site might reduce the impacts of periphyton overgrowth on T. hemprichii and maintain the dominance of T. hemprichii in the community. Our results suggest seagrasses will not necessarily respond to fluctuating environments in the same way in the coming decades.